The Factors Influencing Teachers' Willingness to Remain in Rural Areas After the Expiration of Their Compulsory Service Contract: A Case Study in Enshi Prefecture, Hubei Province, China - Yuanli Dong; Liao Bo-qin; Safdar Abbas; See Hoon Peow; Jian Zhang (Quality in Sport, 2023)
Quality education can only be achieved with the assistance of experienced and qualified teachers. In order to ensure quality education in disadvantaged areas in China, it is necessary to keep experienced teachers in rural areas. This paper investigates factors that could influence rural teachers’ decision to stay or not on teaching at the expiry of their service contract. As a part of project, “Research on rural Teacher Training Mode in Minority Areas of Hubei Province in post-poverty Era “data from 1193 rural teachers who had qualified from a government teacher training programme from selected villages under the jurisdiction of the Enshi Prefecture, Hubei province was collected. As part of the survey, a number of factors are examined that influence a teacher's willingness to stay or leave, as well as remedial measures that are deemed necessary to prevent teachers from leaving. For the analysis of the data, SPSS 25 and AMOS 24 were used. The study found that the teachers have a high willingness to stay on the job after the contract expires. Among the factors contributing to their willingness are the local cultural environment, the local infrastructure attachment to the area, and the school's working environment. Wage income, professional identity, professional development, and school working conditions also play an important role as maintenance factors. There is a direct relationship between the rural infrastructure and a person's willingness to continue working after the expiration of a contract, and there is also direct relationship between the local attachment and the cultural atmosphere of the local community. Local attachment is the dominant factor, the local infrastructure is a secondary improvement area, and salary, promotion of opportunities, respect for teachers and education are in the priority improvement area. Finally, the paper proposes that the retention of rural teachers should be based on the cultivation of local attachment, rural revitalization, improvement of health factors and construction of “UGSR–P” cultivation of community.